PENERAPAN KONSELING COGNITIVE BEHAVIOR THERAPY UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA SMA N 1 GEBOG KUDUS - Sa'adah, Nailis; Sumarwiyah, Sumarwiyah; Kusmanto, Agung Slamet (Universitas Muria Kudus, 2024)
The aim of this research is to determine the factors that cause students' low learning concentration and the application of individual counseling with a Cognitive Behavior Therapy approach to increase students' learning concentration. The type of research used is a qualitative case study. Data collection techniques use observation, interviews, home visits and documentation. The research results prove that the application of cognitive behavior therapy counseling can help increase students' learning concentration at AY and AMI. Before the counseling was carried out, AY and AMI students experienced low learning concentration because they were unable to divide their time between studying, playing and resting. Therefore, AY and AMI counselees have low learning concentration. After individual counseling for three meetings, students AY and AMI Sudha were able to concentrate during the learning process.